A 1-week diet break improves muscle endurance during an intermittent dieting regime in adult athletes: A pre-specified secondary analysis of the ICECAP trial - Peos, J. J.; Helms, E. R.; Fournier, P. A.; Krieger, J.; Sainsbury, A. (PLOS ONE, 2021)
Athletes undergoing energy restriction for weight/fat reduction sometimes apply `diet breaks` involving increased energy intake, but there is little empirical evidence of effects on outcomes. Twenty-six resistance-trained athletes (11/26 or 42% female) who had completed 12 weeks of intermittent energy restriction participated in this study. Participants had a mean (SD) age of 29.3 (6.4) years, a weight of 72.7 (15.9) kg, and a body fat percentage of 21.3 (7.5) %. During the 1-week diet break, energy intake was increased (by means of increased carbohydrate intake) to predicted weight maintenance requirements. While the 1-week diet break had no significant effect on fat mass, it led to small but significant increases in mean body weight (0.6 kg, P<0.001), fat-free mass (0.7 kg, P<0.001) and in resting energy expenditure, from a mean (and 95% confidence interval) of 7000 (6420 to 7580) kJ/day to 7200 (6620 to 7780) kJ/day (P = 0.026). Overall, muscle endurance in the legs (but not arms) improved after the diet break, including significant increases in the work completed by the quadriceps and hamstrings in a maximum-effort 25-repetition set, with values increasing from 2530 (2170 to 2890) J to 2660 (2310 to 3010) J (P = 0.018) and from 1280 (1130 to 1430) J to 1380 (1220 to 1540) J (P = 0.018) following the diet break, respectively. However, muscle strength did not change. Participants reported significantly lower sensations of hunger (P = 0.017), prospective consumption (P = 0.020) and irritability (P = 0.041) after the diet break, and significantly higher sensations of fullness (P = 0.002), satisfaction (P = 0.002), and alertness (P = 0.003). In summary, a 1-week diet break improved muscle endurance in the legs and increased mental alertness, and reduced appetite and irritability. With this considered, it may be wise for athletes to coordinate diet breaks with training sessions that require muscle endurance of the legs and/or mental focus, as well as in the latter parts of a weight loss phase when increases in appetite might threaten dietary adherence.